Peculiarities of Rheumatoid Arthritis with Hereditary Predisposition - Islamova Kamola Akramovna; Abdushukurova Komila Rustamovna (American Journal of Bioscience and Clinical Integrity, 2024)
Objective. The purpose of the work is to study the heredity of rheumatoid arthritis. Material and methods. 100 patients were studied: 88 women and 12 men with RA, with the help of this special questionnaire, the functional state of the joint and the genetic character were determined. Results and discussion. One or more systemic rheumatic diseases were detected in 37% of patients among first- and second-line relatives using the developed program. This allowed us to divide the patients into 2 subgroups: the first group - patients with RA without rheumatic diseases among the relatives (n=63), the second group - patients with hereditary burdened RA (n=37). Conclusion. Thus, in patients with burdened heredity by systemic rheumatic diseases, RA debuted earlier, more often subacutely, with oligoarticular lesions of large joints, but with a tendency to rapidly spread joint syndrome, with a large number of painful and swollen joints, prolonged morning stiffness, which significantly affects the quality of life of these patients. Patients with burdened heredity are more sensitive to emotional, physical overload and hormonal fluctuations.